Investigating the Residual Effects of Chronic Cannabis Use and Abstinence on Verbal and Visuospatial Learning - Lorenzetti, Valentina; Takagi, Michael; van Dalen, Yvonne; Yücel, Murat; Solowij, Nadia (Frontiers in Psychiatry, 2021)
Rationale Regular cannabis users have been shown to differ from non-using controls in learning performance. It is unclear if these differences are specific to distinct domains of learning (verbal, visuospatial), exacerbate with extent of cannabis exposure and dissipate with sustained abstinence. Objective This study examines different domains of learning (verbal, visuospatial) in current and abstaining cannabis users, and the role of chronicity of use. Methods In a cross-sectional design, we examined 127 psychiatrically healthy participants (65 female) with mean aged of 34 years. Of these, 69 individuals were current regular cannabis users (mean 15 years use), 12 were former cannabis users abstinent for ~2.5 yrs (after a mean of 16 years use), and 46 were non-cannabis using controls. Groups were compared on verbal learning performance assessed via the California Verbal Learning Test (CVLT-II) and for visuospatial learning measured with the Brown Location Test (BLT). We explored the association between CVLT/BLT performance and cannabis use levels in current and former users. Results Current cannabis use compared to non-use was associated with worse performance on select aspects of verbal learning (Long Delay Cued Recall) and of visuospatial learning (Retroactive Interference and LD Rotated Recall). Prolonged abstinence was associated with altered verbal learning but intact visuospatial learning. There were non-significant correlations between distinct cannabis use measures, age and learning in both current and former users. Conclusions Our findings suggest cannabis use status (current use, former use) affects different domains of learning (verbal and visuospatial) in a distinct fashion. These findings might be accounted for in the design of cognitive interventions aimed to support abstinence in cannabis users.